Determination of |Vcb| from the semileptonic decay B0 → D*- ℓ+ν - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; et al. (1996)
Semileptonic decays B → D*- ℓ+νX were selected from a sample of 3.1 million hadronic Z decays collected by the DELPHI detector at LEP. A topological search for semileptonic B decays to resonant and non-resonant D*- π+ states was performed and the ratio of the branching fractions: Br(B → D*- ℓ+νX)/Br(B → D*- ℓ+νX) + Br(B0 → D*- ℓ+ν) = 0.19 ± 0.10(stat) ± 0.06(syst) was determined. Taking into account this contribution, the differential decay width of B0 → D*- ℓ+ν was measured as a function of the momentum transfer from the B to the D*- in two separate analyses, using exclusive and inclusive methods of D*- ℓ+ reconstruction. The distributions were fitted over the full momentum transfer range to extract the product of |V cb| times the normalization of the decay form factor F(q max2): F(qmax2)|Vcb| = (35.4 ± 1.9(stat) ± 2.4(syst)) • 10-3. The value of |Vcb| was computed using theoretical calculations of F(q max2), giving: |Vcb| = (38.9 ± 2.0(stat) ± 2.6(syst) ± 1.7(theory)) • 10-3. The total branching fraction Br(B0 → D*- ℓ+ν) was determined to be: Br(B0 → D*- ℓ+ν) = (5.52 ± 0.17(stat) ± 0.68(syst))%.